Blood pressure and risk of subarachnoid hemorrhage in China - McGurgan, I; Clarke, R; Lacey, B; Kong, X; Chen, Z; Chen, Y; Gao, Y; Bian, Z; Li, L; Lewington, S (American Heart Association, 2018)
Background and Purpose — Subarachnoid hemorrhage (SAH) has a high case fatality rate and young mean age at onset compared with other types of stroke, but the etiology of SAH is not fully understood. We examined associations of systolic and diastolic blood pressure with incident non-traumatic SAH in a large prospective study in China. Methods — In 2004-2008, 512 891 adults (59% female) from the general population were recruited into the China Kadoorie Biobank. Participants were interviewed, measured, and followed up for fatal and non-fatal events. After excluding those with prior vascular disease, Cox regression analysis was used to relate blood pressure to incident SAH events. Analyses were adjusted for major confounders and corrected for regression dilution to give associations with long-term average (usual) blood pressure. Results — At baseline, mean age was 51 (SD 11) years, and mean systolic blood pressure (SBP)/diastolic blood pressure (DBP) was 130.6/77.6 (SD 21.0/11.1) mmHg. During 3.5 million person-years of follow-up, there were 553 incident SAH cases (mean age at event 61 [SD 11] years), yielding an overall annual incidence rate of 12.9 per 100 000. Usual blood pressure was linearly and positively associated with higher risk of incident SAH: 10 mmHg higher usual SBP and 5 mmHg higher usual DBP were associated with hazard ratios (HR) for SAH of 1.21 (95% CI: 1.13-1.29) and 1.20 (95% CI: 1.12-1.28), respectively. There was no evidence that the HR varied by age or sex, or by levels of other vascular risk factors. Elevated blood pressure (SBP >120 mmHg) accounted for 23% of all SAH cases. Conclusions — The incidence of SAH in China was comparable with estimates from Western populations. Higher levels of blood pressure were positively associated with higher risks of SAH, and elevated blood pressure accounted for about a quarter of all SAH cases.